PENGARUH DESTINATION IMAGE DAN TOURIST EXPERIENCE TERHADAP REVISIT INTENTION YANG DIMEDIASI OLEH PERCEIVED VALUE PADA DESTINASI WISATA HALAL DI KOTA BANDA ACEH - Nelly Agustin Fadiryana; Syafruddin Chan (Departemen Manajemen, Universitas Syiah Kuala, 2019)
AbstractThis study aims to determine the effect of destination image and tourist experience to the revised intention mediated by perceived value. The sample consists of 150 domestic and overseas tourists who visit and have the intention of returning to Halal tourism destination city of Banda Aceh. The sampling technique used nonprobability sampling method with purposive sampling. Data collection was done through survey by questionnaire method. This study used analytical technique of Structural Equation Model (SEM), which is estimated by Analysis of Moment Structure (AMOS) is a statistical method selected to describe the observed variables. The result shows that the destination image is not significant to the perceived value, the tourist experience has significant effect on the perceived value, the destination image is not significant to the revisit intention, the tourist experience significantly influences the revisit intention, the perceived value has significant effect on revisit intention, direct destination image to revisit intention mediated by perceived value, there is indirect influence of tourist experience to revisit intention mediated by perceived value, there is influence of domestic tourists smaller than foreign tourists in moderating influence of tourist experience to perceived value, there is influence domestic tourists are smaller than tourists abroad in moderating the influence of tourist experience on the revisit intention, there is no influence of domestic tourists smaller than tourists outside country in moderating the effect of perceived value on the revisit intention.Keywords Destination Image, Tourist Experience, Perceived Value, Revisit Intention,Domestic Tourists and Foreign Tourists, Halal Tourism, Banda Aceh.